PEMBERDAYAAN PEDAGANG KAKI LIMA DALAM MENINGKATKAN SANITASI ALAT MAKAN DAN PERSONAL HYGIENE DI SENTRA WISATA JAMBANGAN SURABAYA - Hermiyanti, Pratiwi; Suryono, Hadi; ., Narwati (Health Community Engagement, 2023)
The Jambangan culinary tourism center consist of 20 booth selling snacks consisting of food and beverages managed by Dinas Koperasi Kota Surabaya. The presence of visitors from various walks of life requires hygienic management so that it does not have the potential to cause disease transmission caused by food/drinks eaten. Unhealthy food can be caused by the presence of microbes in food and the surrounding environment, unqualified personal hygiene of traders, unhealthy food processing, equipment used that does not meet health requirements. This service activity is one of the efforts made in minimizing microbial contamination on cutlery, one of which is by utilizing kaffir lime leaves as a natural disinfectant with a concentration of 100 mg/100 ml which can minimize the number of germs on cutlery by 79%. Another effort that supports solving the problem of the presence of E.coli contamination is by changing individual healthy behavior habits carried out by traders, namely personal hygiene.